Legal Pluralism in Bugis-Makassar Society: Negotiating Interfaith Dynamics, Islamic Law, Ammotere Abbaji, and Restorative Justice in Silariang Cases - Azwad Rachmat Hambali; Zainuddin; Salle; Muhammad Nur Ikram Fuady; Rafika Nur (Contemporary Issues on Interfaith Law and Society, 2026)
The enforcement of administrative restrictions on interfaith marriage following Supreme Court Circular (SEMA) No. 2/2023 has triggered a rise in silariang (elopement) cases in South Sulawesi, risking communal conflict due to clashing triadic jurisdictions (state, Islam, and adat). This study aims to conceptualize Ammotere Abbaji as a culturally embedded victim-offender mediation mechanism within Bugis-Makassar customary law and design a model for its integration into the national criminal justice system. Utilizing an empirical legal method within a qualitative socio-legal framework, this study gathered primary data through a series of in-depth interviews with key informants in South Sulawesi (including customary leaders, religious figures, and law enforcement officers), validated through source triangulation and non-participant observation of tudang sipulung communal deliberations. The qualitative analysis was theoretically reinforced by a secondary review of the sociometric mathematical modeling of marital disputes. The results indicate that Ammotere Abbaji substantively merges the ethical values of Siri’ na Pacce and Islamic Ishlah principles to facilitate organic community-level conflict resolution. However, this customary settlement remains impeded by dual-processing at the police level and administrative registration barriers. This study concludes the necessity of designing a three-level (normative, procedural, and rights-protection) 'Restorative Pluralism Framework' (RPF) under the substantive Penal Code (Law No. 1/2023) and the new Criminal Procedure Code (Law No. 20/2025) to guarantee the protection of women's agency and a just interfaith legal diversity governance.